PARTAI GERINDRA DALAM KONTESTASI PERPOLITIKAN DI BALI TAHUN 2008 – 2019 - SIAHAAN, JERICO; SUWITHA, I PUTU GEDE; ASMARIATI, ANAK AGUNG INTEN (Jurnal Ilmiah Widya Sosiopolitika; Vol 3 No 1 (2021): MEDIA, POLITIK, DAN PANDEMIDO - 10.24843/JIWSP.2021.v03.i01.p05, 2021)
ABSTRACT This study will take the theme of Political History with the topic "Gerindra Party in Political Contest in Bali, 2008 - 2019.” In this paper, the research proposal that the author adopts, namely the Gerindra Party which has a" Nationalist - Democratic "breath can contest politically in Bali, as for the problems that will be disclosed as follows: (1). How do the Gerindra party in Bali play in the General Election; (2). Why is there a Gerindra party political contestation in the elections in Bali; (3). What are the implications of the Gerindra Party in the Political Contest in Bali. Then the methodology that the author uses in this writing is political history, social history, and finally the history of thought. The results of this study indicate that the presence of Gerindra in 2008, and also its participation in the 2009 political events at the national and provincial levels, has provided a political style with a spirit of nationalism in politics in Indonesia, especially in Bali. The hard work JURNAL ILMIAH WIDYA SOSIOPOLITIKA E-ISSN 2685-4570 61 built into the vision and mission of the party bearing the head of the Garuda, has planted its roots so that it can be recognized by the Balinese people. The programs campaigned by Gerindra are considered to be included in the priority problems of the country at this time. Gerindra is a party with a platform, Nationalist - Popular. Why? The proof that Gerindra gives to the community is that Gerindra will always compete in defending the interests of the people in order to create the welfare of the people at large. Gerindra's success in increasing party electability in the 2009, 2014 and 2019 elections has provided enormous public enthusiasm, Gerindra is able to demonstrate its existence in the annual political events at both the regional elections and the legislative level, Gerindra is also able to accommodate people's aspirations regarding based economic issues. tourism as a development sector for the advancement of society in Bali. In reorganizing political commodification in Bali, Gerindra also seeks to see the political map of any area in Bali as the value and focus of winning Gerindra's candidates. Talking about the implications of Gerindra being able to provide potential for the political, social and legal development sector, 11 years of this contribution was built by Gerindra to transform the level of public trust in the sustainability of the Gerindra party in Bali, both at the city and provincial regency levels. Keywords : Gerindra Party, Contestation, Nationalist - Democratic, Cadres of party members, Bali.